The Impact of Teacher Workload on Students' Academic Achievement in the Context of Science, Technology, and Buddhism - Tursinah Anggendari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This qualitative research aims to investigate the influence of teacher workload on students' academic achievement, particularly within the unique framework of science, technology, and Buddhism. Employing a phenomenological research model, the study delves into the lived experiences of teachers and students in educational settings infused with Buddhist principles alongside science and technology education. The sampling technique involves purposive sampling, selecting participants with diverse backgrounds and experiences. Data analysis follows thematic analysis methods, identifying patterns and themes within the collected narratives. Preliminary findings suggest a complex interplay between teacher workload, students' academic outcomes, and the integration of Buddhist perspectives within the curriculum. Understanding these dynamics can offer insights into optimizing teaching practices and curriculum design to enhance student learning outcomes in science, technology, and Buddhist-oriented educational contexts.